Cellulase, Pectinase, and Xylanase Production by Listeria sp. ISH 16 using Coffee Pulp Waste Medium - Ummi Wasilah; Kahar Muzakhar; Purwatiningsih Purwatiningsih (IPTEK Journal of Proceedings Series, 2020)
In this study, microbial utilization of coffee pulp waste to produce three carbohydrases (cellulase, pectinase, and xylanase) has been investigated. An isolate Listeria sp. ISH-16 which grown in liquid medium containing 0.5% coffee pulp alkali extract can grow well with density of reach 107 x 58.5 cell/mL. Further, the culture can optimum produced of pectinase after 72 hours incubation at 37oC, but for cellulase and xylanase longer 84 hours incubation needed. The harvested of crude pectinase, cellulase and xylanase had activity 0.15, 0.23, and 0.61 unit/ ml after dialysis, respectively. All enzymes stable at a range of pH 4-5.5, but they work optimum at different pH. Of each enzyme pectinase, cellulase, and xylanase work optimum at pH 5, 4.5, and 5.5. based on these results, it may be adopted as a strategy to produce enzymes with low cost so that further investigation such as large scale and purification enzyme is needed.